2018
DOI: 10.1111/hae.13507
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered molecules for the management of haemophilia: Promise and remaining challenges

Abstract: Recombinant DNA technology has led to accelerating introduction of novel therapeutics for the treatment of haemophilia. This technology has driven the development of recombinant clotting factors, extended half-life clotting factors, alternative biologics to promote haemostasis and enabled the launch of the gene therapy era for haemophilia. At the core of this technology is the ability to study the structure and function of the native molecules and to apply rational bioengineering to overcome limitations to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The past decade has seen a burgeoning of innovative treatment options for haemophilia,32 33 ranging from recombinant next generation clotting factors with longer half-lives, to a wide range of new approaches and modalities, such as the new subcutaneously administered bispecific antibody mimicking factor VIII that binds to activated factor IX, which in turn activates factor X. Other new developments include liver targeted siRNA, which can result in a large enough knockdown of the antithrombin gene to allow significant haemostasis, and an antibody against a tissue factor pathway inhibitor that also enhances haemostasis 34…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…The past decade has seen a burgeoning of innovative treatment options for haemophilia,32 33 ranging from recombinant next generation clotting factors with longer half-lives, to a wide range of new approaches and modalities, such as the new subcutaneously administered bispecific antibody mimicking factor VIII that binds to activated factor IX, which in turn activates factor X. Other new developments include liver targeted siRNA, which can result in a large enough knockdown of the antithrombin gene to allow significant haemostasis, and an antibody against a tissue factor pathway inhibitor that also enhances haemostasis 34…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…A growing number of factor replacement products, including extended half‐life (EHL) products, have been evaluated in previously treated patients (PTPs) with ≥150 EDs and approved for the management of hemophilia A. Products are currently being evaluated in clinical trials of PUPs or minimally treated patients (MTPs) in which the primary endpoint is inhibitor development (Table ).…”
Section: Novel Factor Productsmentioning
confidence: 99%
“…The review also discusses the approach to diagnosis, education, and comprehensive care within the hemophilia treatment center (HTC). References addressing the history of hemophilia, long‐term management, pharmacokinetic testing for personalized factor replacement, and novel therapies are listed in Table …”
Section: Critical References For Modern Hemophilia Carementioning
confidence: 99%
“…Among many EHL rFVIII products that have been evaluated in clinical trials, rFVIIIFc (Efmoroctocog alpha, Eloctate ® ) was the first one to be approved for the treatment of patients with HA, both for prophylaxis and for treatment for bleeding episodes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This drug is the first representative of a new pharmacological class (EHL rFVIII), and pharmacokinetic studies on adults have demonstrated a 1.5-fold increase in half-life compared with full-length rFVIII [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%